Some features of the pale sea urchin (Strongylocentrotus pallidus) biology in Peter the Great Bay (Japan Sea) - Maria O. Chalienko; Marianna V. Kalinina (Известия ТИНРО, 2017)
Population of pale sea urchin Strongylocentrotus pallidus in Peter the Great Bay is investigated. The samples for its size structure and distribution were collected at the depth from 5 to 700 m in July 2013, 2014 and in April 2015 and the samples for the state of gonads, intestines and age structure - at the depths of 41, 69, 280, 346, and 670 m in early April 2015. The size structure at different depths is significantly different: the large individuals with average size of 70.0 mm (portion of commercial ones 98 %) occupy mainly the middle shelf area with the depths of 55-100 m, deeper at the depths of 100-200 m the portion of commercial urchins is lower (67 % in 2014 and 92 % in 2015), and the continental slope (depth > 200 m) is occupied by mainly (77-96 %) non-commercial individuals with average size of 35.5 mm. Age of sea urchins was determined by the growth zones on plates of their shells processed by Jensen method and varied from 3 to 12 years. The growth rate of sea urchins from the shelf areas was approximately in 1.5 times higher as compared with those from the continental slope, primarily due to different conditions of feeding. The gonads cellular composition was defined for the samples of 50 cells per female. The cells were differentiated in the categories of oocytes proliferation, oocytes differentiation, and mature eggs, and the gonad maturity stage was determined by domination of these categories, taking into accounts the S. pallidus reproductive cycle. In spring, the sea urchins from the shelf areas (depths of 41 and 69 m) were generally more mature as compared with those from the continental slope (depths of 280 and 346 m). However, correlation between the gonadal index and depth of habitat was not significant because the mature females were sampled in any depth. Composition of intestinal content and food components were determined visually, looking the bolus under binocular microscope. The sea urchins intestines were mostly filled with detritus at the depth of 41 m, sponges (Suberites sp.) at the depth of 69 m (70 % of cases), and unedible substances as silt and sand at the depth of 280, 346 and 670 m, minor fractions were the algal litter, remains of crustaceans, and detritus.